A Novel Deep Eutectic Solvents Synthesized by Solid Organic Compounds and Its Application on Dissolution for Cellulose - Zhou, Erpeng; Liu, Huiru (Asian Journal of Chemistry, 2014)
This study developed a new area of novel molten salt prepared by solid organic compounds, named deep eutectic solvents. Three deep eutectic solvents were synthesized by urea/caprolactam, caprolactam/acetamide and urea/acetamide at the molar ratio of 1:3, 1:1 and 1:2, respectively. The physical characters such as melt point, conductivity and solubility were investigated. It was shown that they were significantly affected by the mole ratio of the organic compounds and three systems at 1:3, 1:2 and 1:1 gave a liquid with the freezing point of 30, 48 and 18 °C, respectively, which were much lower than those of raw materials. The conductivity in the range 10-5 to 10-4 S/m changed with the temperature and accorded to Arrhenius equation. IR showed that the H-bondings of raw materials were disappeared and new H-bondings were formed. The application of three deep eutectic solvents on the dissolution for cellulose was investigated. It was found that the solubility of cellulose was low. The dissolving process for cellulose was the competition of deep eutectic solvents with the H bonding in cellulose. New H-bonding was formed between the hydroxy of cellulose and the oxygen of carbonyl and/or the nitrogen of amino group.